2002
DOI: 10.1074/jbc.m204354200
|View full text |Cite
|
Sign up to set email alerts
|

Selective Binding of Synapse-associated Protein 97 to GluR-A α-Amino-5-hydroxy-3-methyl-4-isoxazole Propionate Receptor Subunit Is Determined by a Novel Sequence Motif

Abstract: A family of four closely related PDZ domain-containing membrane-associated guanylate kinase homologues (MAGUKs) is involved in the regulation of the amount and functional state of ionotropic glutamate receptors in excitatory synapses. To understand the mechanisms that determine the specificity of these interactions, we examined the structural basis of the highly selective association between the ionotropic GluR subunit GluR-A and synapse-associated protein 97 (SAP97). The C terminus of GluR-A bound to the PDZ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
104
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(111 citation statements)
references
References 28 publications
7
104
0
Order By: Relevance
“…The C-terminal PDZ binding motifs of these channels, as well as nearby upstream amino acids, probably contribute to their specific association with different protein complexes. Supporting this idea, the peptide sequence SSG, which lies upstream of the PDZ binding motif in the GluR1 AMPA receptor, confers selective binding to SAP97 (77). Interestingly, Kir2.2 also contains this sequence in roughly the same upstream location.…”
Section: Fig 6 Syntrophin Associates With Kir2 Channels In Vivo Amentioning
confidence: 75%
“…The C-terminal PDZ binding motifs of these channels, as well as nearby upstream amino acids, probably contribute to their specific association with different protein complexes. Supporting this idea, the peptide sequence SSG, which lies upstream of the PDZ binding motif in the GluR1 AMPA receptor, confers selective binding to SAP97 (77). Interestingly, Kir2.2 also contains this sequence in roughly the same upstream location.…”
Section: Fig 6 Syntrophin Associates With Kir2 Channels In Vivo Amentioning
confidence: 75%
“…These domains are specialized, regulatable motifs that facilitate colocalization of proteins in specialized microdomains such as the PSD. One of the PDZ domains of SAP97 interacts with the PDZ domain on the C terminus of the AMPA receptor GluA1 subunit in GluA1/GluA2 hetero-oligomers (Cai et al, 2002;Leonard et al, 1998).…”
Section: Ampa Subtype Of Glutamate Receptor Traffickingmentioning
confidence: 99%
“…Taken together, our present findings suggest that hDlg is recruited to the plasma membrane by TEM5 and scaffolds it in endothelial cells during tumor angiogenesis and neoangiogenesis. It is known that hDlg scaffolds some receptors and ion channels in neurons, T lymphocytes, and cardiac myocytes (Kim et al, 1995;Kim and Sheng, 1996;Hanada et al, 1997;Leonard et al, 1998;Murata et al, 2001;Cai et al, 2002), but the function of hDlg in endothelial cells has not yet been reported. This is the first identification of the transmembrane protein, which binds to hDlg, in endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, hDlg, like Dlg, is likely to be involved in the negative regulation of cell proliferation. Furthermore, hDlg directly binds alpha-amino-3-hydroxy-5-methyl-4-isoxazole propionic acid (AMPA) receptors and Shaker-type K þ channels via its PDZ domain and scaffolds them at synapses (Kim et al, 1995;Kim and Sheng, 1996;Leonard et al, 1998;Cai et al, 2002). hDlg binds Shaker-type K þ channels in T lymphocytes and cardiac myocytes (Hanada et al, 1997;Murata et al, 2001).…”
Section: Introductionmentioning
confidence: 99%